Enabling fast-charging via layered ternary transition metal oxide as anode materials for lithium-ion batteries - Yannis De Luna (14778250) (2025)
Lithium-ion batteries remain at the forefront of battery technology – however, a new generation of electrode materials is required to satisfy new demands in large-scale and more advanced energy storage systems. The application of transition metal niobates as battery anode material has attracted research interest due to their higher operating voltage, capacities, and rate capabilities compared to niobium oxides and conventional graphitic anodes. Current battery technology utilizes cobalt as part of the electrode material, which is one of the most expensive transition metals with strained supplies from the growing demand for electric vehicles. As a way to distribute the use of transition metals, ternary transition metal oxides may have great potential for more cost-effective and high-rate anode materials. In this work, a ternary transition metal oxide based on Ni, Mn, and Nb has been synthesized through a mechanochemical synthesis method at a relatively lower calcination temperature (<1000 °C). The as-prepared Ni-Mn-Nb anode was characterized and electrochemically evaluated as an anode material against Li/Li+ (half-cell) and against NMC and LFP cathodes (full cells). For comparison, niobium pentoxide and binary transition metal oxides (Ni-Nb and Mn-Nb) were also prepared and tested as anode materials. The first discharge and charge capacities delivered by Ni-Mn-Nb anode at 0.1 A g-1 were 550 and 400 mAh g-1, respectively. The ternary metal oxide design greatly enhanced its cycling performance after 7000 cycles with a reversible capacity of 93.8 mAh g-1 at a high current density of 2 A g-1 (10C) - the highest among the other anode materials in this work at a very high rate, synonymous to fast-charging. Post-mortem analysis revealed a stable SEI layer on the anode after cycling, which enabled the extremely stable cycling in 7000 cycles. Other Information Published in: Materials Research Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.materresbull.2025.113325